Saksi Pelaku yang Bekerjasama pada Pengungkapan Kasus Tindak Pidana Pembunuhan Berencana dalam Sistem Peradilan Pidana (Studi Putusan Nomor: 798/PID.B/2022/PN.JKT.SEL) - Larumpa, Renaldi Markus; Malik, Faissal; Anshar, Anshar (UNES Law Review, 2023)
This research aims to determine and analyze the regulations regarding cooperating perpetrator witnesses as the basis for judicial consideration in determining the status of cooperating perpetrator witnesses in the disclosure of premeditated murder cases in decision number 798/Pid.b/2022/PN.Jkt.Sel. Additionally, the study explores the extent of the involvement of cooperating perpetrator witnesses in general criminal offenses as a form of legal discovery. The research method employed is normative research using a case and legal approach to analyze primary legal materials, such as the court decision number 798/Pid.b/2022/PN.Jkt.Sel, and the Law No. 31 of 2014, SEMA 4 of 2011, and Joint Regulations of 2011. The results of the research indicate that, first: the regulation of cooperating perpetrator witnesses applies only to specific criminal offenses as mentioned. However, the judge's considerations in the a quo decision state that the Defendant Eliezer deserves to be designated as a cooperating perpetrator witness in the premeditated murder case based on the explanation in Article 5 Paragraph (2) of Law No. 31 of 2014 and later other conditions in Article 28 Paragraph (2). Second: Due to the complexity of disclosing serious and organized general criminal cases (casuistic), the conditions regarding the types of penalties are expanded for general criminal offenses with specified limitations.